Methods for health economic evaluation of complex interventions in healthcare: current practice, challenges and guidance for future research - Chernyak, Nadja; Mohebbi, Damon; Alayli, Adrienne; Behrens, Johann; Eckhardt, Helene; Henschke, Cornelia; Holle, Rolf; Kairies-Schwarz, Nadja; Liersch, Sebastian; Möhler, Ralph; Müller, Dirk; Neumann, Anja; Vomhof, Markus; Zechmeister-Koss, Ingrid; Köberlein-Neu, Juliane; Icks, Andrea (Das Gesundheitswesen, 2025)
Health economic methods can support the development and evaluation of new healthcare interventions by generating data on the resources used and relating these to a defined benefit. However, the standard methodology of health economic evaluation that is usually used does not do justice to the high degree of complexity of interventions in healthcare. As a result, there is a lack of decision-relevant information, for example, on the preferences of the target group, on spillover effects on the part of carers, or on implementation costs and the role of different contexts in the implementation of interventions into routine care. The UK Medical Research Council’s (MRC) standard-setting framework for complex interventions therefore emphasises the need to incorporate health economic aspects more strongly into all phases of the development and evaluation of complex interventions. To make this possible, the MRC’s recommendations for expanding and adapting the standard methodology of health economic evaluation must be concretised and supplemented. Building on already established methodological procedures, recommendations should be developed and proposals for necessary further research formulated.Gesundheitsökonomische Methoden können die Entwicklung und Evaluation von neuen Versorgungskonzepten unterstützen, indem sie Daten zu eingesetzten Ressourcen genieren und diese ins Verhältnis zu einem definierten Nutzen setzen. Die meist angewendete Standardmethodik der gesundheitsökonomischen Evaluation wird dabei jedoch dem hohen Komplexitätsgrad von Interventionen in der Gesundheitsversorgung nicht gerecht. Dadurch fehlen entscheidungsrelevante Informationen, beispielsweise zu Präferenzen der Zielgruppe, zu Spillover-Effekten auf Seiten pflegender Angehöriger, oder zu Implementierungskosten und der Rolle unterschiedlicher Kontexte bei der Überführung von Interventionen in die Regelversorgung. Das Standard setzende Rahmenwerk des britischen Medical Research Councils (MRC) für komplexe Interventionen betont daher die Notwendigkeit, gesundheitsökonomische Aspekte stärker in alle Phasen der Entwicklung und Evaluation komplexer versorgungsbezogener Interventionen einzubeziehen. Um dies zu ermöglichen müssen die Empfehlungen des MRC zur Erweiterung und Anpassung der Standardmethodik der gesundheitsökonomischen Evaluation konkretisiert und ergänzt werden. Aufbauend auf bereits etablierten methodischen Verfahren sollen hierzu Empfehlungen entwickelt sowie Vorschläge für erforderliche weitere Forschung formuliert werden.
Keywords: Health economic evaluation; Complex interventions; MRC framework